Predicting postinterventional rupture of intracranial aneurysms using arteriography-derived radiomic features after pipeline embolization - Ma, Chao; Liang, Shikai; Liang, Fei; Lu, Ligong; Zhu, Haoyu; Lv, Xianli; Yang, Xuejun; Jiang, Chuhan; Zhang, Yupeng (Frontiers in Neurology, 2024)
Background and purpose: Postinterventional rupture of intracranial aneurysms (IAs) remains a severe complication after flow diverter treatment. However, potential hemodynamic mechanisms underlying independent predictors for postinterventional rupture of IAs remain unclear. In this study, we employed arteriography-derived radiomic features to predict this complication.We included 64 patients who underwent pipeline flow diversion for intracranial aneurysms, distinguishing between 16 patients who experienced postinterventional rupture and 48